Avaliação e validação dos critérios utilizados para a adoção de serviços em nuvem nas organizações pós pandemia COVID-19 - Santos Junior, Fernando Manoel Alves dos (2023)
With the demand boost and protagonism of cloud computing services, the organizations are increasingly dependent on up-to-date and structured information for making the right decision in adopting and continuing the partnership with providers. The main objective of the research is to bring a classified list of all criterias that influence organizations in choosing a cloud service and in their strategy in the continuity of the adoption with the great social changes imposed by the COVID-19 pandemic, to evaluate and validate the effects caused by the adoption and prioritization of these services. The literature shows that the topic has been increasingly approached since 2016 and most of the research is always validated through questionnaires with a quantitative approach. In this context, the result presented here brings a summary of the criteria addressed, presents what are the topics in evidence in all the material available in the bases of the literature and compares it in a classified format with the current view of organizations through a survey applied twice in the same public seeking the pre and post COVID-19 pandemic criteria classification, enabling a better evaluation of providers by the decision makers of organizations and the future direction of their strategies through academic material with these classifications and respective weights of each of the criteria over the others listed .